Modelling the impact of HIV and hepatitis C virus prevention and treatment interventions among people who inject drugs in Kenya. (1st December 2022) - Stone, Jack; Fraser, Hannah; Walker, Josephine G.; Mafirakureva, Nyashadzaishe; Mundia, Bernard; Cleland, Charles; Bartilol, Kigen; Musyoki, Helgar; Waruiru, Wanjiru; Ragi, Allan; Bhattacharjee, Parinita; Chhun, Nok; et al.
Abstract : Objectives: People who inject drugs (PWID) in Kenya have high HIV (range across settings: 14–26%) and hepatitis C virus (HCV; 11–36%) prevalence. We evaluated the impact of existing and scaled-up interventions on HIV and HCV incidence among PWID in Kenya. Design: HIV and HCV transmission model among PWID, calibrated to Nairobi and Kenya's Coastal region. Methods: For each setting, we projected the impact (percent of HIV/HCV infections averted in 2020) of existing coverages of antiretroviral therapy (ART; 63–79%), opioid agonist therapy (OAT; 8–13%) and needle and syringe programmes (NSP; 45–61%). We then projected the impact (reduction in HIV/HCV incidence over 2021–2030), of scaling-up harm reduction [Full harm reduction ('Full HR'): 50% OAT, 75% NSP] and/or HIV (UNAIDS 90–90–90) and HCV treatment (1000 PWID over 2021–2025) and reducing sexual risk (by 25/50/75%). We estimated HCV treatment levels needed to reduce HCV incidence by 90% by 2030. Results: In 2020, OAT and NSP averted 46.0–50.8% (range of medians) of HIV infections and 50.0–66.1% of HCV infections, mostly because of NSP. ART only averted 12.9–39.8% of HIV infections because of suboptimal viral suppression (28–48%). Full HR and ART could reduce HIV incidence by 51.5–64% and HCV incidence by 84.6–86.6% by 2030. Also halving sexual risk could reduce HIV incidence by 68.0–74.1%. Alongside full HR, treating 2244 PWID over 2021–2025 could reduce HCV incidence by 90% by 2030. Conclusion: Existing interventions are having substantial impact on HIV and HCV transmission in Kenya. However, to eliminate HIV and HCV, further scale-up is needed with reductions in sexual risk and HCV treatment.